2018
DOI: 10.1093/ckj/sfy118
|View full text |Cite
|
Sign up to set email alerts
|

Causes and risk factors for acute dialysis initiation among patients with end-stage kidney disease—a large retrospective observational cohort study

Abstract: Background Patients who require acute initiation of dialysis have higher mortality rates when compared with patients with planned starts. Our primary objective was to explore the reasons and risk factors for acute initiation of renal replacement therapy (RRT) among patients with end-stage kidney disease (ESKD). Our secondary objective was to determine the difference in glomerular filtration rate (GFR) change in the year preceding RRT between elective and acute dialysis starts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Acute KRT initiation was a main reason for almost half of respondents who (had) received CHD. Half of the patients starting dialysis experience an unplanned or acute start [40][41][42] that may hinder adequate training and preparation for home dialysis or pre-emptive KTx. However, patients facing an acute start of KRT may still be able to receive home dialysis or KTxeven if only at a later stage-if they receive adequate education and support [43].…”
Section: Discussionmentioning
confidence: 99%
“…Acute KRT initiation was a main reason for almost half of respondents who (had) received CHD. Half of the patients starting dialysis experience an unplanned or acute start [40][41][42] that may hinder adequate training and preparation for home dialysis or pre-emptive KTx. However, patients facing an acute start of KRT may still be able to receive home dialysis or KTxeven if only at a later stage-if they receive adequate education and support [43].…”
Section: Discussionmentioning
confidence: 99%
“…It has to be considered that a relevant proportion of ESRD is not preventable or cannot be optimally prepared for renal replacement therapy with preventive nephrologic services. This is on the one hand due to rapid and unpredictable decline in renal function or acute health conditions (21,22). On the other hand, progression to ESRD occurs in some patients despite best therapeutic efforts.…”
Section: Meaning Of the Results And Comparison With Literaturementioning
confidence: 99%
“…That was the ultimate goal of this study. Past research has shown that older age, male gender, increased comorbidity burden, diabetes, cardiovascular disease (e.g., congestive heart failure), and hypertension are associated with late referral to nephrologist care and suboptimal dialysis initiation (18)(19)(20)(21). The lack of recent nephrologist care also has been found to be a significant predictor of suboptimal dialysis starts (21).…”
Section: Discussionmentioning
confidence: 99%